Chainmail co-catalyst of NiO shell-encapsulated Ni for improving photocatalytic CO2 reduction over g-C3N4. Issue 16 (1st April 2019) - Han, Chunqiu; Zhang, Rumeng; Ye, Yinghao; Wang, Li; Ma, Zhaoyu; Su, Fengyun; Xie, Haiquan; Zhou, Ying; Wong, Po Keung; Ye, Liqun
Abstract : The chainmail co-catalyst NiO shell-encapsulated Ni increased the separation efficiency of photogenerated carriers in g-C3 N4 . Therefore, Ni/NiO/g-C3 N4 showed improved photocatalytic activity in CO2 reduction. Abstract : Nickel element cannot exist stably on its own, but with an bared of an NiO shell, nickel element can realize desirable stable existence. Herein, Ni 2+ was photoreduced to Ni particles and deposited on graphite carbon nitride (g-C3 N4 ) under vacuum. The surface of Ni particles was oxidized to form an NiO shell after the samples were exposed to air, and elemental Ni was protected by the encapsulation of the NiO shell to realize the coexistence of Ni and NiO. The chainmail co-catalyst of NiO shell-encapsulated Ni over g-C3 N4 (Ni/NiO/g-C3 N4 ) was prepared and applied in the photocatalytic reduction of CO2 and showed the best photocatalytic activity when the Ni/NiO loading was 3 wt%. After illumination for 2 h, the CO generation rate reached a value of 27.9 μmol g −1 h −1, which was about nine times that of pure g-C3 N4 . The steady-state surface photovoltage spectrum (SPV), ultrafast spectrum of transient photovoltage (TPV) and time-resolved photoluminescence (PL) spectra as well as electrochemical tests showed that Ni/NiO/g-C3 N4 has a low recombination rate of photogenerated electron–hole pairs. In situ Fourier transform infrared spectroscopy (FT-IR) and DFT calculations were used to explain the photocatalytic mechanism at the molecular level.